Treatment of Distillery Industrial Wastewater Using Ozone Assisted Fenton’s Process: Color and Chemical Oxygen Demand Removal with Electrical Energy per Order Evaluation - Perumal Asaithambi; Mamuye Busier Yesuf; Seifu Kebede Debela; Rajendran Govindarajan; N. M. Hariharan; Esayas Alemayehu (International Journal of Chemical Engineering)
Ozonation is one of the most effective and efficient advanced oxidation processes (AOPs) and has shown great potential in the treatment of industrial effluent and wastewater. In the present work, the ozone-Fenton process for % COD and color removal together with electrical energy per order (EE/O) determination for distillery industrial wastewater (DIW) was established. The process was developed by combining the ozone (O3) with the Fenton (Fe2+/H2O2) process. The ozone-Fenton (O3/Fe2+/H2O2) was compared with other treatment processes such as O3, Fe2+, H2O2, O3/Fe2+, O3/H2O2, and Fe2+/H2O2 for EE/O together with % COD and color removal efficiency for DIW. The removal of color at 100% and chemical oxygen demand (COD) of 96.875% were achieved with a minimum of EE/O of 0.5315 kWh/m3 using the O3/Fe2+/H2O2 process by operating at optimum conditions. The % COD and color values obtained using O3/Fe2+/H2O2 were significantly higher than those obtained using O3, Fe2+, H2O2, O3/Fe2+, O3/H2O2, and Fe2+/H2O2 processes. The % color, % COD removal, and its associated EE/O were evaluated by varying Fe2+, H2O2, O3 inlet and COD concentration, and initial wastewater pH using the O3/Fe2+/H2O2 process. The synergy effect of the O3 and Fe2+/H2O2 processes was evaluated and reported. Our experimental findings suggest that combining O3 with the Fe2+/H2O2 process could effectively treat industrial effluent and wastewater.